Muscovite neocrystallization and synchronous quartz dynamic recovery in shear zones: In situ Rb Sr and U Pb dating from the Cap de Creus (Eastern Pyrenees, Spain) - Clémence Nicolas; Valérie Bosse; Yoann Denèle; Olivier Merle; Emmanuel Gardés; Caroline Lotout; Jean-Luc Devidal; Mathis Neimard; Christian Nicollet; Paul Wiesen; Etienne Médard; Françoise Roger (Tectonophysics, 2026)

Cellulose nanocrystals-supported organocatalyst for the synthesis of cyclic carbonates via cycloaddition of carbon dioxide to epoxide - Nouaamane El Idrissi; Hicham Aitbella; Nicolas Merle; Frédéric Cazaux; João P. Prates Ramalho; Larbi Belachemi; Hamid Kaddami; Philippe Zinck (Carbohydrate Polymers, 2025)

Microbiological risk factors, ICU survival, and 1-year survival in hematological patients with pneumonia requiring invasive mechanical ventilation - Benjamin Seybold; Timo Funk; Peter Dreger; Gerlinde Egerer; Juliane Brandt; Carsten Mueller-Tidow; Nicola Giesen; Uta Merle (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose To identify pathogenic microorganisms and microbiological risk factors causing high morbidity and mortality in immunocompromised patients requiring invasive mechanical ventilation due to pneumonia. Methods A retrospective single-center study was performed at the intensive care unit (ICU) of the Department of Internal Medicine at Heidelberg University Hospital (Germany) including 246 consecutive patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia from 08/2004 to 07/2016. Microbiological and radiological data were collected and statistically analyzed for risk factors for ICU and 1-year mortality. Results ICU and 1-year mortality were 63.0% (155/246) and 81.0% (196/242), respectively. Pneumonia causing pathogens were identified in 143 (58.1%) patients, multimicrobial infections were present in 51 (20.7%) patients. Fungal, bacterial and viral pathogens were detected in 89 (36.2%), 55 (22.4%) and 41 (16.7%) patients, respectively. Human herpesviruses were concomitantly reactivated in 85 (34.6%) patients. As significant microbiological risk factors for ICU mortality probable invasive Aspergillus disease with positive serum-Galactomannan (odds ratio 3.1 (1.2-8.0), p = 0.021,) and pulmonary Cytomegalovirus reactivation at intubation (odds ratio 5.3 (1.1–26.8), p = 0.043,) were identified. 1-year mortality was not significantly associated with type of infection. Of interest, 19 patients had infections with various respiratory viruses and Aspergillus spp. superinfections and experienced high ICU and 1-year mortality of 78.9% (15/19) and 89.5% (17/19), respectively. Conclusions Patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia showed high ICU and 1-year mortality. Pulmonary Aspergillosis and pulmonary reactivation of Cytomegalovirus at intubation were significantly associated with negative outcome.

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Thermodynamics of Calcium binding to the Calmodulin N-terminal domain to evaluate site-specific affinity constants and cooperativity - Maria Rosa Beccia; Sandrine Sauge-Merle; David Lemaire; Nicolas Brémond; Romain Pardoux; Stéphanie Blangy; Philippe Guilbaud; Catherine Berthomieu (JBIC Journal of Biological Inorganic Chemistry, 2015)